Innovative Honey-Based Product and Its Beneficial Effects Measured by Modern Biophysical and Imaging Skin Techniques - Grzegorz Suwiński; Izabela Nowak (Pharmaceuticals)
Background: Honey is widely recognized for its potential benefits in skincare, yet its incorporation into formulations is challenging due to its stickiness. This study aimed to evaluate the effects of hand creams with varying concentrations of multifloral honey (0%, 5%, 10%, and 15% w/w) on skin parameters and to assess their application characteristics. Methods: A total of 24 volunteers were divided into two groups, each receiving a blinded pair of creams (0%/10% or 5%/15% honey) to apply on their left and right hands. Instrumental methods (Corneometer®, Tewameter®, Cutometer®, Visioscan®, and Visioline®) were used to measure skin parameters at the baseline, 15 min after the first application, and after 4 weeks of regular use. Sensory characteristics were evaluated through participant questionnaires. Results: After 4 weeks, honey-infused creams showed notable improvements in skin moisturization (up to 29.7%), smoothness (up to 21.3%), wrinkle area reduction (up to 21.4%), and mean wrinkle depth reduction (up to 11.7%). Among these, the increases in moisturization and reductions in wrinkle depth were statistically significant compared to the placebo. The sensory evaluations revealed no significant differences between formulations, highlighting the vehicle’s effectiveness in minimizing the stickiness typically associated with honey. Conclusions: This study highlights the efficacy of honey-enriched hand creams in enhancing skin parameters over time while maintaining favorable sensory characteristics. These findings support the use of honey in dermatological formulations and provide insights into overcoming its formulation challenges.